2016
DOI: 10.1002/cctc.201601077
|View full text |Cite
|
Sign up to set email alerts
|

Divanadium‐Substituted Phosphotungstate Supported on Magnetic Mesoporous Silica Nanoparticles as Effective and Recyclable Catalysts for the Selective Oxidation of Alcohols

Abstract: A new magnetically recyclable catalyst (Fe3O4@mSiO2/NH‐PV2W) was fabricated by immobilizing divanadium‐substituted Keggin phosphotungstic acid H5PV2W10O40 on mesoporous‐silica‐coated Fe3O4 core–shell nanoparticles by a facile procedure. The magnetic core–shell nanoparticles were prepared by coating a thin mesoporous silica shell directly on pristine magnetic Fe3O4 and functionalized with amino radicals simultaneously. Then the active H5PV2W10O40 was immobilized on the mesoporous silica shell of the Fe3O4 core–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…The FT‐IR spectra of as‐prepared Fe 3 O 4 , Fe 3 O 4 @TiO 2 , Fe 3 O 4 @TiO 2 @PDA/SiW 11 V, Fe 3 O 4 @TiO 2 @PDA/SiW 11 V−Ag samples are compared in Figure 2, as well SiW 11 V and PDA. For the pristine Fe 3 O 4 magnetite core, the band at 584 cm −1 is assigned to the stretching vibration of Fe−O bonds (Figure 2a) [17] . After introducing TiO 2 shell, the absorption region extends to 954 cm −1 owing to Ti−O−Ti stretching vibrations (Figure 2b) [3e] .…”
Section: Resultsmentioning
confidence: 99%
“…The FT‐IR spectra of as‐prepared Fe 3 O 4 , Fe 3 O 4 @TiO 2 , Fe 3 O 4 @TiO 2 @PDA/SiW 11 V, Fe 3 O 4 @TiO 2 @PDA/SiW 11 V−Ag samples are compared in Figure 2, as well SiW 11 V and PDA. For the pristine Fe 3 O 4 magnetite core, the band at 584 cm −1 is assigned to the stretching vibration of Fe−O bonds (Figure 2a) [17] . After introducing TiO 2 shell, the absorption region extends to 954 cm −1 owing to Ti−O−Ti stretching vibrations (Figure 2b) [3e] .…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [149] [141] tal results showed that the FST microspheres had high photocatalytic activity under ultraviolet light, and the degradation rate of methyl orange reached 95.0%. Then Li et al further prepared a new hollow network magnetic Fe 3 O 4 /SiO 2 /mTiO 2 (FSmT) composite microsphere photocatalyst by using network Fe 3 O 4 as the magnetic layer, dense SiO 2 layer as the electronic barrier and mesoporous TiO 2 as the active layer.…”
Section: Photocatalysis Applicationsmentioning
confidence: 99%
“…different organic transformations [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. However, to date, few magnetite nanoparticles supported palladium catalysts have been prepared and successfully used in the aerobic oxidation of alcohols.…”
Section: Accepted Manuscriptmentioning
confidence: 99%